2015
DOI: 10.3390/ijgi4020447
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Urban Growth Using a Random Forest-Cellular Automata (RF-CA) Model

Abstract: Sustainable urban planning and management require reliable land change models, which can be used to improve decision making. The objective of this study was to test a random forest-cellular automata (RF-CA) model, which combines random forest (RF) and cellular automata (CA) models. The Kappa simulation (KSimulation), figure of merit, and components of agreement and disagreement statistics were used to validate the RF-CA model. Furthermore, the RF-CA model was compared with support vector machine cellular autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
80
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 63 publications
(109 reference statements)
1
80
0
2
Order By: Relevance
“…This approach demonstrated an improvement when compared to the logistic-CA model in terms of urban simulation accuracy. A random forest based CA model was used to simulate urban growth in Harare Metropolitan Province, Zimbabwe from 1984 to 2013 [24]. This model outperformed CA models based on support vector machine (SVM) and logistic regression in the study area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach demonstrated an improvement when compared to the logistic-CA model in terms of urban simulation accuracy. A random forest based CA model was used to simulate urban growth in Harare Metropolitan Province, Zimbabwe from 1984 to 2013 [24]. This model outperformed CA models based on support vector machine (SVM) and logistic regression in the study area.…”
Section: Introductionmentioning
confidence: 99%
“…One important issue in CA modeling is the quantification of the impacts of the factors that drive urban growth and land use change at both global and local scales. Many approaches have been developed to define CA transition rules and each is aimed at improving the overall accuracy and reducing errors of simulation [21][22][23][24]. These approaches vary widely in theoretical assumptions, underlying methodologies, and spatio-temporal resolutions and extents [25].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the most common method to assess simulation results was visual inspection by experts [18,24,25], however this is highly subjective and irreproducible. Several methods have been proposed over the last decade, all of which compare simulated maps with maps of assumed truth [12][13][14][15][16][17]26]. There is continued debate over accuracy assessment methodologies among land change and remote sensing research foci, with the sole emphasis on quantity and allocation disagreement [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation of normal distribution assumption, robustness to over-fitting, less required training time and providing information regarding variable importance are the main characteristics of this method. Kamusoko and Gamba (2015) compared the random forest-cellular automata (RF-CA) with support vector machine cellular automata (SVM-CA) and logistic regression cellular automata (LR-CA) models for modelling urban change. They found that RF-CA model outperformed SVM-CA and LR-CA models.…”
Section: Introductionmentioning
confidence: 99%